Supply chain strategies in the context of an ecommerce chain (E-Chain) - Reis, João Gilberto Mendes dos; Costa Neto, Pedro Luiz de Oliveira; Fusco, José Paulo Alves [UNESP]; Machado, Sivanilza Teixeira (Independent Journal of Management and Production, 2014)
This paper purpose to explore the relationships between supply chain strategies and product performance in retail e-commerce. In this case, we concern that in current, in order to bear up under competition, organizations have to manage their supply chains so that they meet the needs of their final customers. With this concept in mind, the research presented in this study focuses on establishing the right strategy for supply chains according to their product segment. Thus, after a Literature Review, the paper explain a methodology based in different authors studies. Finally the article focuses on a pratical case in e-commerce retail that describes its application in this field. The research shows that it is possible to use a methodology for classifying supply chains using chain strategies and product features. The use of the right strategy for supply chains will improve the competitive advantage of businesses. One limitation is that the methodology study focuses on only two e-commerce segment; future studies may go further in refining the proposed framework for other segments. The aim of this research is to offer businesses a model for evaluating supply chains, allowing them to improve the performance of their products and services by using the right strategy for supply chains. The classification proposal of this paper presents an original model for classification of supply chains based on different studies on the theme.
Keywords: E-commerce; Supply chain management; Innovative; Functional products